Hubungan Pola Makan Dengan Kejadian Gastritis Pada Santri Di Pondok Pesantren Al-Mukmin Sukoharjo - , Rifqiyatunnasiyah, Irdawati S.Kep., Ns., M.Si.Med (2017)
Gastritis is an inflamation process of the mucosa and submucosa stomach. Gastritis can occur in people who have bad and irregular eating patterns and consume foods that can stimulate the production of stomach acid. The purpose of this study is to examine the relationship between eating pattern with the incidence of gastritis in student in Al-Mukmin Boarding School Sukoharjo. This is a quantitative research with descriptive research type, the approach used in this research is cross sectional. The sample of this research is second and third grader in boarding school of Al-Mukmin Sukoharjo in 2016 (2 and 3 graderof junior high school) amounted to 70 respondents, taken using proportional random sampling technique. Instruments in this study is a questionnaire or questionnaire made by the researchers themselves and used in dietary variables. This questionnaire is in the form of a closed question compiled with a Likert scale for, containing 17 questions about diet (type, portion, and feeding frequency) consisting of favorable and unfavorable questions.The analysis result relation between eating pattern with the incidence of gastritis with the chi square test obtained value x237.718and p value 0.001, the concluded there was a relation between eating pattern with the incidence of gastritis. The recommendation for further research is expected to examine other variables suspected to be associated with gastritis.